'Iñche kai che': settler colonialism and erasing the past in Gülumapu/Chile. (2nd January 2023) - Sauer, Jacob J.
ABSTRACT: Setter colonialism is dedicated to the elimination of the native, not just from territory but from the past. This form of elimination comes from the mistranslation or misunderstanding of names and terms that identify individuals and communities, which the colonists then use to separate Indigenous peoples from their own pasts. Many researchers have argued that the modern Mapuche are the result of ethnogenesis in the late eighteenth century, in part from misuse of the Mapuche language mapuzugun in describing communities in the past. This paper argues that, based on ethnographic, archaeological, and historic evidence, Che is the correct autonym to use for the Indigenous inhabitants of Wajmapu, the territory comprised of southern Chile and western Argentina, before the Che themselves began using the autonym Mapuche in the eighteenth century.